2021
DOI: 10.1016/j.joms.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of the Condylar Hypoplasia and Facial Asymmetry in Craniofacial Microsomia Using Cone-Beam Computed Tomography

Abstract: Purpose: To assess the condylar hypoplasia and its correlation with craniofacial deformities in adults with unilateral craniofacial microsomia (CFM).Methods: Pretreatment cone-beam computed tomography scans of consecutive adults (mean age: 20.4 § 3.0 years; range: 17.3 to 31.4 years) with Pruzansky-Kaban type I and IIA CFM were reconstructed in 3D. Both condyles were segmented. Asymmetry ratios (affected side/contralateral side) of condylar volume were calculated to indicate the extent of condylar hypoplasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…To determine the sample size, the G-Power software (version 3.1.9.7; Franz Faul, University of Kiel, Kiel, Germany) was used. A minimum of 17 subjects per group was estimated based on our previous studies [17,18] by setting an effect size of 1.0, a significance level of 5% (p < 0.05), and a power of 80%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the sample size, the G-Power software (version 3.1.9.7; Franz Faul, University of Kiel, Kiel, Germany) was used. A minimum of 17 subjects per group was estimated based on our previous studies [17,18] by setting an effect size of 1.0, a significance level of 5% (p < 0.05), and a power of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D head models were registered in a cephalometric reference frame based on the protocol of Swennen et al, using the landmarks orbitale and porion on the non-affected side, and further completed by the frontozygomatic points, nasion, and sella (Fig. 1) [16,17]. The affected side was defined as the side to which the chin deviation was pointed to and where CFM was present.…”
Section: Image Acquisition and Cephalometrymentioning
confidence: 99%
“…According to previous studies, we know that the affected TMJs are hypoplastic. For example, Chen et al18 investigated 14 patients with type IIa HFM and found that the ratios of asymmetry for height and volume in the affected condyles were 40.69% and 18.16%, respectively. In another study, Zhang et al20 reported that for each type of HFM, sex, and sidedness had no impact on the condylar volume on either side.…”
Section: Discussionmentioning
confidence: 99%
“…9 The primary locus of asymmetry in HFM is believed to be the condyle. 18 After birth, the mandibular bony structure increases in size and exhibits changes in shape, predominantly due to condylar displacement, superficial bony apposition, and resorption. 19 Understanding the morphologic characteristics of the TMJ in HFM and the morphologic changes post-MDO in detail is of significant value for the diagnosis and treatment of HFM.…”
Section: Discussionmentioning
confidence: 99%
“…The primary locus of asymmetry in HFM is believed to be the condyle. 1 Understanding the morphological characteristics of the TMJ in HFM more profoundly and clearly is of significant value for diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%